The Mediating Role of Student Motivation in the Linking of Perceived School Climate and Achievement in Reading and Mathematics - Fan, Weihua; Williams, Cathy (Frontiers in Education, 2018)
While the current literature provides valuable insight into how school climate and student motivation impact academic achievement, Research examining the mediating effects of motivation in the linking of school climate perceptions and achievement is limited. The current study employed structural equation modeling to examine a model that illustrates the role of self-efficacy and intrinsic motivation in the linking of student perceptions of school climate to reading and mathematics achievement. Analysis used data from the Educational Longitudinal Study of 2002 (ELS: 2002) that were gathered in a survey conducted by the National Center for Education Statistics (NCES, 2004) and are representative of a national sample of 14,639 10th grade students. The results showed that the hypothesized model fit the data well supporting the hypothesis that student self-efficacy and intrinsic motivation play a mediating role in the linking of perceptions of school climate with reading and mathematics achievement. Additionally, students’ perceptions of school climate related significantly with both achievement outcomes, and perceptions of school climate concerning teacher/student relationship related significantly with all motivation variables both self-efficacy and intrinsic motivation.